Cultural hegemony : how ideologies on gender are propagated through the new media platform - YouTube Singapore - Ramachandran Palanisamy (2015)
This paper looks at how dominant gender ideologies are (re)produced in the new media in Singapore, particularly in YouTube using Hall’s theory on encoding. A total of 388 videos were analyzed and 6 YouTube content producers were interviewed. Even though YouTube is made out to be an alternative to traditional media such as television, the alternative is only in form and style rather than in ideology. Videos analyzed contained elements of dominant gender ideology, namely patriarchy, gender roles, compulsory heterosexuality and objectification of women. Interviews of content producers on YouTube also revealed that (re)production of dominant gender ideologies was a result of factors external to content producers such as viewers, advertisers, sponsors, sources of ideas, government policies and nature of ownership of YouTube channel.